High-Performance Microbial Fuel Cell for Aromatic Hydrocarbon Bioremediation: Leveraging a Unique Mangrove-Derived Electrogenic Consortium - de Souza, João Carlos; Zani, Ana Clara Bonizol; Silva, João Pedro [UNESP]; dos Santos, Amanda; de Aragão Umbuzeiro, Gisela; Bueno, André Valente; Lobo, Fernanda Leite; Reginatto, Valeria; de Andrade, Adalgisa Rodrigues (American Chemical Society (ACS), 2025)
Enhancing bioelectrocatalytic activity to increase the efficiency of toxic compound biodegradation and energy generation continues to be a critical challenge in bioelectrochemical systems. In this context, the present study aimed to obtain a novel electrogenic microbial consortium, sourced from mangrove sediments, capable of improving microbial fuel cell (MFC) performance in both energy generation and aromatic compound's biodegradation. This new microbial consortium was tested in dual-chamber MFCs designed for the biodegradation of benzene, employed as a model aromatic compound. Overall, the results demonstrated that the enrichment of a microbial community derived from mangrove sediments in the southeastern region of Brazil (State of Espírito Santo) significantly enhanced bioelectricity generation in MFCs via benzene biodegradation. During the initial acclimation phase using 1000.0 mg L-1 sodium acetate, the bacterial genera Arcobacter (20.2%) and Comamonas (11.0%) were predominant. As sodium acetate was progressively replaced and the MFC operated solely with benzene (330.0 mg L-1), Bacillus (32.9%) and Arcobacter (30.3%) became the dominant genera. The MFC exhibited remarkable efficiency, achieving 98.7 ± 2.4% benzene removal within 96 h, while the output voltage increased from 568.0 ± 10.3 mV to 902.3 ± 20.6 mV as the feedstock shifted from sodium acetate to benzene. The maximum power density, Coulombic efficiency, and MFC cumulative energy efficiency were 390.1 ± 26 mW m-2, 14.4%, and 17.8%, respectively, surpassing previously established benchmarks and improving power density by approximately 100-fold compared to other devices. In conclusion, this innovative electrogenic microbial consortium, characterized by its unique bacterial diversity, markedly enhanced electron transfer, voltage, power density, and current generation in MFCs. It represents a highly promising and sophisticated approach for both substantial bioelectricity production and the effective bioremediation of aromatics, especially benzene, a compound known for its extreme toxicity, mutagenicity, and carcinogenicity.